Impact of Accountability and Transparency on Achieving SDG 4 in Indonesia - Gabriela Citra Bunga’allo; Muhammad Iqbal; Selmita Paranoan; Lucyani Meldawati (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
The primary objective of this research is to evaluate how the openness and responsibility inherent in regional financial disclosures contribute to reaching SDG 4 targets across Indonesia. By examining these governance factors, the study clarifies their role in supporting national educational progress. The study used panel data from 34 provinces for the 2021–2024 period, with a total of 136 observations. Data were obtained from the Supreme Audit Agency (BPK), the Central Statistics Agency (BPS), BAPPENAS, and official local government websites. The analysis was conducted using the Generalized Least Squares (GLS) method with a Random Effect Model (REM) approach. The results show that accountability has a positive and significant effect on the achievement of SDG 4. These findings indicate that the quality of local government financial accountability can improve the effectiveness of education budget management. Transparency also has a positive and significant effect, with a more dominant effect than accountability. Openness of financial information encourages public oversight, increases the efficiency of budget use, and strengthens the implementation of education policies. Simultaneously, accountability and transparency have been proven to support the achievement of SDG 4. The research findings strengthen the perspective of good governance and agency theory in the context of regional financial governance.